The effects of venlafaxine on depressive-like behaviors and gut microbiome in cuprizone-treated mice - Du, Chunhai; Zhang, Tian; Feng, Chong; Sun, Qian; Chen, ZhiGuo; Shen, Xin; Liu, Ying; Dai, Gengwu; Zhang, Xuan; Tang, Nailong (Frontiers in Psychiatry, 2024)
Background: Cuprizone (CPZ) treated mice show significant demyelination, altered gut microbiome, and depressive-like behaviors. However, the effects of venlafaxine (Ven) on the gut microbiome and depressive-like behavior of CPZ-treated mice are largely unclear.Methods: Male C57BL/6J mice were fed a chow containing 0.2% cuprizone (w/w) for 5 weeks to induce a model of demyelination. Meanwhile, the gut microbiota and depressive-like behaviors were assessed after mice were fed with Ven (20 mg/kg/day) or equal volumes of distilled water for 2 weeks by oral gavage from the third week on during CPZ treatment.Results: CPZ treatment decreased the sucrose preference rate in the sucrose preference test (SFT) and increased immobility time in the tail-suspension test (TST), and it also induced an abnormality in β-diversity and changes in microbial composition. Ven alleviated the depressive-like behavior and regulated the composition of the gut microbiota, such as the increase of Lactobacillus and Bifidobacterium in CPZ-treated mice.The anti-depressant effects of Ven might be related to the regulation of gut microbiota in the CPZ-treated mice.